Trabecular variation in the first metacarpal and manipulation in hominids. Issue 2 (24th November 2019) - Dunmore, Christopher J.; Bardo, Ameline; Skinner, Matthew M.; Kivell, Tracy L.
Abstract: Objectives: The dexterity of fossil hominins is often inferred by assessing the comparative manual anatomy and behaviors of extant hominids, with a focus on the thumb. The aim of this study is to test whether trabecular structure is consistent with what is currently known about habitually loaded thumb postures across extant hominids. Materials and methods: We analyze first metacarpal (Mc1) subarticular trabecular architecture in humans ( Homo sapiens, n = 10), bonobos ( Pan paniscus, n = 10), chimpanzees ( Pan troglodytes, n = 11), as well as for the first time, gorillas ( Gorilla gorilla gorilla, n = 10) and orangutans ( Pongo sp., n = 1, Pongo abelii, n = 3 and Pongo pygmaeus, n = 5). Using a combination of subarticular and whole‐epiphysis approaches, we test for significant differences in relative trabecular bone volume (RBV/TV) and degree of anisotropy (DA) between species. Results: Humans have significantly greater RBV/TV on the radiopalmar aspects of both the proximal and distal Mc1 subarticular surfaces and greater DA throughout the Mc1 head than other hominids. Nonhuman great apes have greatest RBV/TV on the ulnar aspect of the Mc1 head and the palmar aspect of the Mc1 base. Gorillas possessed significantly lower DA in the Mc1 head than any other taxon in our sample. Discussion: These results are consistent with abduction of the thumb during forceful "pad‐to‐pad" precision grips in humans and, in nonhuman great apes, a habitually adducted thumb that is typically used in precision and power grips. This comparative context will help infer habitual manipulative and locomotor grips in fossil hominins.